HMPA-Catalyzed One-Pot Multistep Hydrogenation Method for the Synthesis of 1,2,3-Trisubstituted Indolines - Zhu, R.; Liang, Q. Y.; Gong, Y. M.; Pu, Q. Y.; Wang, Z. Y.; Wang, C.; Zhou, L.; Sun, J. (Synlett, 2018)
A convenient and facile method was developed for the synthesis of 1,2,3-trisubstituted indolines. Starting from indole derivatives and ketones/aldehydes, the corresponding indoline products could be obtained with high yield by the hexamethylphosphoramide (HMPA) catalyzed indole Friedel–Crafts reaction, reduction and direct reductive amination process.
Keywords: cascade reaction; reductive animation; HMPA; trichlorosilane; indole; indoline